Recommendations for biostatisticians in managing and conducting medical research consultations - Bujang, Mohamad Adam; Ab Rahman, Jamalludin (Institute for Clinical Research, NIH, Ministry of Health Malaysia, 2020)
One of the determining factors for a successful research output is the design of the research itself. Thus, a researcher, a methodologist or an epidemiologist and a biostatistician may each have his/her own perspective of how to optimize the design of research, by playing an active role in both planning and conducting the research. Therefore, this e-book emphasizes the importance of the role of a biostatistician in managing and conducting research consultations mainly for research that revolves around the medical field.